The Development of a Training Course on the Development of Innovative School Curriculum of Secondary schools in the Eastern Economic Corridor - Techawattanasiridumrong, Wacharapatr (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This research aims to 1) study the needs of the development of innovative school curriculum, 2) develop and find the effectiveness of training courses, and 3) study the satisfaction of the training courses. Methods for researching the nature of research and population development are teachers and educational personnel. Secondary schools in the Eastern Economic Corridor of the Eastern Region included 920 students. The samples were teachers and educational personnel. 30 secondary schools in the Eastern Economic Corridor. The research instruments were questionnaires, training courses. Knowledge test And satisfaction questionnaire The statistics used for data analysis were percentage, mean, standard deviation. And the t-value test The results of the research were as follows: 1) Teachers and educational personnel need innovative school curriculum development. The overall picture is at a high level. The average value was 4.41. 2) The training program consisted of 7 components: training objectives, content, and structure, duration of training activities. Training materials Measuring and evaluating learning outcomes The training courses were as effective as 79.10/80.28, and the teachers and educational personnel who received the training had higher scores on the knowledge of the development of the innovative school curriculum after the training was higher than before the training. With statistical significance at the level. 01 and 3) teachers and educational personnel. The overall satisfaction with the training courses was at the highest level.